1989
DOI: 10.1002/jat.2550090605
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐related proximal tubular dysfunction in male rats chronically exposed to lead

Abstract: Male Wistar rats were given 0.5 and 2% lead acetate in drinking water for 2 months, 1% lead acetate for 3 months and sodium acetate equimolar to 2% lead acetate for 3 months. Glucose, total proteins, lactate dehydrogenase (LDH), lysozyme and beta 2-microglobulin (beta 2-m) were measured in 24-h urine every month. Kidney weight and histology were also examined. At the three doses, lead exposure produced a significant elevation of the kidney weight. No significant change in urinary parameters was observed in rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 16 publications
0
19
1
Order By: Relevance
“…1). Histologic changes include eosinophilic intranuclear indusions in proximal tubular cells consisting of lead-protein complexes, and mitochondrial swelling (29)(30)(31)(32)(33). Renal manifestations of acute lead poisoning have been well described both in animal models and in humans; these include glycosuria, aminoaciduria (34,35), and phosphaturia, collectively representing the Fanconi syndrome (36)(37)(38).…”
Section: Lead Nephropathymentioning
confidence: 99%
“…1). Histologic changes include eosinophilic intranuclear indusions in proximal tubular cells consisting of lead-protein complexes, and mitochondrial swelling (29)(30)(31)(32)(33). Renal manifestations of acute lead poisoning have been well described both in animal models and in humans; these include glycosuria, aminoaciduria (34,35), and phosphaturia, collectively representing the Fanconi syndrome (36)(37)(38).…”
Section: Lead Nephropathymentioning
confidence: 99%
“…Several researchers have reported nephrotoxic effects in animals fed various doses of lead (Vyskocil et al 1989), and studies conducted in humans (Bennet 1985) and children (Hu 1991) have indicated that high levels of lead exposure may impair renal function. The renal toxicity of lead is closely related to its selective accumulation in the kidneys (Choie and Richter 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Maruhn et al (1983) 39) and Vyskocil (1995) 40) have proposed that increased excretion of LDH in urine occurs after exposure to lead acetate along with a profound increase in kidney weight. Urinary β-Glucuronidase derives from the lysosomes of tubular cells and from the epithelial cells of urinary tract.…”
Section: Discussionmentioning
confidence: 99%